Rhythmodynamics and the “Fate of Events”: Projection Theatre as an Experimental Platform for Artists - Voronina, Oksana Iu. (Actual Problems of Theory and History of Art, 2025)
The paper considers the Projection Theatre as one of the important phenomena in the contextual field of the Society of Easel Artists. The Projection Theatre, which emerged among the first abstract theatres in Russia in 1922, was created by the artists themselves and became part of the life-building project of the Avant-garde of the 1920s. The study established that the concept of projectionism proposed by the first director of the theatre Solomon Nikritin was subsequently followed by Sergei Luchishkin. Luchishkin became one of the main members of the Society of Easel Artists, and at the same time he directed the theatre from 1926 until 1930, which almost completely coincided with the time of OST’s activity on the art scene. According to Luchishkin, the Projection Theatre he developed was intended to decipher modernity and “tune” the viewer in a certain way, literally, in a physical sense, charge him with the help of “rhythmodynamics” brought to perfection. Other OST artists searched to embody the same thing, only through painting or graphics. In both theater and painting, a new mobile artistic integrity emerged as an important element for the Society of Easel Artists. The performance, just like the picture, had to embody a “plastically developing construction.” This became possible thanks to the OST members’ favorite principle of dynamic montage. As the study shows, the practice of the Projection Theater turned out to be extremely important for the appearance of several original features in OST painting. This includes the desire for all-encompassingness, a world as if newly created, and characters as if mastering the algorithms of movement for the first time, distinguished by a purely functional appearance, characters necessary for revealing the properties of space (often thought of as global). The Projection theatre, which was invariably called “new” by its creators, was supposed to reveal the “world connection” of phenomena. Meanwhile, the actor, trained according to the directors’ authorial methodology and playing many roles in the same performance, was supposed to demonstrate that the characters were merely “material for the development of events.”
Keywords: Projection Theatre; Solomon Nikritin; Sergei Luchishkin; rhythmodynamics; montage; Society of Easel Artists; OST; easel painting of the 1920s